Women's influence on the private life of society in Late Antiquity according to Saint Augustine - E.V. Anokhina (Ученые записки Казанского университета: Серия Гуманитарные науки)
This article considers the forms of women’s influence in Saint Augustine’s “Confessiones” that are realized through the sphere of private life. The analysis of the historical context revealed that Late Antiquity, characterized by continuity and transitivity, was marked by a coexistence of the ancient and Christian traditions. Interestingly, it was natural that these traditions became intertwined in the mindset of a person. The gender-marked expressions used by Saint Augustine were studied, and the conclusion was made that he appears to more stick to the ancient ideas about femininity/masculinity, including the belief that women, who were perceived as physically and emotionally imperfect, must be placed under the control of men, i.e., they should obey stronger persons. Simultaneously, the dualism of Saint Augustine’s thinking was noted: he was a striking representative of Late Antiquity, thus he placed religion above gender and the Christian wife above her pagan husband. The main types of influence exerted by women on men were highlighted in accordance with the established instruments of such influence: emotional impact and sexual attachment. From the results obtained, it was summed up that the views of Saint Augustine on women’s influence correlate with his gender-related ideas, as well as with his moral principles.